Lithuanian Deaf and Hard of Hearing Viewers’ Preferences for Sound and Music Indications in Subtitles - Motiejūnienė, Jurgita; Huber, Loreta; Hofmanaitė, Dovilė (Respectus Philologicus, 2025)
In a world where audiovisual media plays a central role in communication, information, and entertainment, ensuring accessibility for all viewers, including deaf or hard-of-hearing, is essential. For these audiences, subtitles are not only a means of following dialogue but also a crucial tool for experiencing sound and music, which are often key to the narrative of media content. The aim of the study is to explore and identify effective strategies for subtitling sounds and music in audiovisual media that meet the preferences and needs of the Lithuanian deaf and hard-of-hearing audience. The empirical research approach adopted for this investigation is based on semi-structured interviews with the deaf and hard-of-hearing participants and qualitative data analysis. The results reveal that the target audience prefers strategies that incorporate minimal use of colour and mixed positioning for both sound and music indication, specifically, a sound source indicated in the brackets at the centre bottom of the screen, the genre and/or the instrument represented by a note symbol at the bottom of the screen, and song lyrics transcribed verbatim and marked with the note symbol.